The Effects of Asymmetric Oil Price Shocks on the Saudi Consumption: An Empirical Investigations - Algaeed, Abdulaziz Hamad (International Journal of Energy Economics and Policy, 2017)
The purpose of this paper is to analyze theoretically and empirically the relationship between the asymmetric oil price shock and the consumption in Saudi Arabia for the period 1985-2015.This paper follows Mehra and Petersen (2005), Zhang and Broadstock (2014), and has added a new perspective through which the oil price shocks are transmitted to consumption in the Saudi economy. The oil price shock is calculated, as SOPI, using GARCH (1,1). VAR and VEC models are applied, and the findings confirm that the oil price shocks affect positively ( +) the earnings of oil, and thereby total consumption. An increase in oil price will cause an increase in revenues, and hence consumption and vice versa. However, the decline in oil revenue on average is about (-21) percent, whereas the fall in consumption is about (-24) percent. These results coincide with the causality tests. Although, Mehra and Petersen (2005) found negative impacts of oil price shocks, our results differ in sign because this work is concerning an oil-exporting country. Keywords: Consumption, Saudi Arabia, Asymmetric shocks, and GARCH. JEL Classifications: C5, E21